Timely care for age-related macular degeneration: a qualitative study among retina specialists in Israel - Vicki Myers; Osnat Luxenburg; Rachel Wilf-Miron; Hani Levkovitch Verbin (BMC, 2024)
Abstract Background Age-related macular degeneration (AMD) affects quality of life and independence, and its incidence and prevalence are increasing due to ageing of the population. Access to effective timely treatment can improve vision and reduce incidence of blindness. This study aimed to explore the perspectives of ophthalmologists in the Israeli public healthcare system regarding timely treatment of AMD patients. Methods Qualitative semi-structured interviews were conducted in 2020-2021 with 22 senior ophthalmologists, from 10 general hospitals and from two HMOs, representing different geographic regions. All interviewees specialize in retinal diseases and work with AMD patients. Interviews discussed patient pathways involved in the diagnosis and treatment of AMD, access to care, and obstacles to timely care. Thematic analysis was conducted. Results Based on the interviews, we describe the usual referral and treatment pathways. Themes included regional disparities, long wait times in some areas, a lack of retina specialists, differences in referral pathways, inappropriate use of emergency department to obtain timely treatment, and second-line treatment not fully covered by insurance, most affecting the weakest segments of the population. Conclusions Loss of vision incurs high health and societal costs. In the context of insufficient medical manpower in Israel, the healthcare system will need to assess future resources to cope with accumulating burden of AMD cases over time in an ageing population. Precise referral information, and simultaneous referral to imaging and retinal clinics, may minimize delays in treatment. Awareness of AMD symptoms and the importance of early intervention could be highlighted by campaigns, particularly among high-risk groups. Highlights • Interviews with hospital-based and community ophthalmologists showed regional disparities in AMD treatment, with long wait times and a lack of retina specialists in some areas. • Differences in referral pathways, inappropriate use of emergency department to obtain timely treatment, and second line treatment not fully covered by insurance were highlighted. • The healthcare system will need to assess future resources to cope with accumulating burden of AMD cases over time in an ageing population • Precise referral information, and simultaneous referral to imaging and retinal clinics, may minimize delays in treatment. • Awareness of AMD symptoms and the importance of early intervention should be emphasized in high-risk groups.